Numerical investigation of application of an embedded cross-flow Fan for STOL performance enhancement - Dhiman, Nikita (2018)
Cross Flow Fans (CFF) had mostly found its application in the Heating, Ventilation and Air Conditioning systems in the industry. In recent years, CFF had been extensively studied in Aerospace industry as a flow control device to prevent flow separation and as propulsive unit in aerial vehicles. In this thesis, a configuration of an embedded CFF was investigated for STOL performance enhancement. The study examined suitable numerical solvers, turbulence model and physical models needed for the simulation. An unsteady sliding mesh solver with Coupled algorithm was found to be suitable for analysis. Turbulence model of Spallart-Allmaras was found to be suitable for VTOL analysis while k-ω SST model was found suitable for STOL analysis having external flow. For VTOL analysis, the normal force of the embedded CFF in the airfoil increased with increase in the RPM of the fan. For external flow analysis, higher RPM of the CFF provided better performance of the fan with 82.3% increase in the normal force (lift) for wind speed of 8 m/s and CFF RPM of 4000 at 0° Angle of attack.